Lack of expression of an alternative CD20 transcript variant in circulating B cells from patients with pemphigus. Issue 1 (30th December 2013) - Gamonet, Clémentine; Ferrand, Christophe; Colliou, Natacha; Musette, Philippe; Joly, Pascal; Girardin, Marie; Humbert, Philippe; Aubin, François
Abstract: We have identified a spliced mRNA transcript of CD20 (named D393‐CD20) which was associated with resistance to RTX in primary B cell from patients with lymphoma and leukaemia. In the present work, we wished to investigate whether D393‐CD20 variant was expressed by B cells from patients with pemphigus. Ten patients with bullous pemphigoid and twenty‐five patients with pemphigus were included. All patients were responder to conventional immunosuppressive agents or rituximab ( n = 11). Efficacy of B‐cell activation by pokeweed mitogen was assessed by CD86 expression using a FACS Canto II flow cytometer. mRNA CD20 expression study was then performed using RT‐PCR assay allowing first to discriminate wild‐type (wt)‐CD20 and D393‐CD20 transcript. Although wt‐CD20 expression was always detected, we were unable to detect D393‐CD20, even after B‐cell activation or RTX treatment. Our results suggest that D393‐CD20 transcript may be a molecular marker of B‐cell malignancies rather than autoimmune disease like pemphigus. Further study of RTX non‐responders or non‐escaping PV patients is thus still required to appreciate whether D393‐CD20 expression may be detected under the pressure of RTX therapy.